Catatonia and cannabis withdrawal: A case report. Issue 1 (2nd January 2016) - Caudron, Mathieu; Rolland, Benjamin; Deheul, Sylvie; Geoffroy, Pierre Alexis; Thomas, Pierre; Amad, Ali
ABSTRACT: Background : Catatonia is a severe motor syndrome found in approximately 10% of all acute psychiatric hospital admissions. It can occur in various psychiatric diseases. The authors report the first case report of catatonia during cannabis withdrawal. Case Presentation : Mr. A, a 32-year-old man, reported to have smoked approximately 20 g of cannabis daily since the age of 11. Mr. A was incarcerated and was reported 3 weeks later to the medical department for having completely ceased talking and eating. At admission in the authors' department, the patient presented with classical catatonia symptoms (Bush-Francis Catatonia Rating Scale [BFCRS] score = 39/69). All laboratory results and brain magnetic resonance imaging (MRI) were normal. Six weeks after his admission and treatments by lorazepam and memantine, his BFCRS score was 0/69. Discussion : This single case study highlights the previously underreported emergence of physical and motor symptoms following cannabis withdrawal. Pathophysiological aspects of abrupt cannabis cessation contributing to γ-aminobutyric acid (GABA)/glutamate balance dysregulation and to catatonia are discussed.